2001
DOI: 10.1118/1.1406514
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a cone‐beam reconstruction algorithm for the single‐circle source orbit with embedded misalignment correction using homogeneous coordinates

Abstract: We present an efficient implementation of an approximate cone-beam image reconstruction algorithm for application in tomography, which accounts for scanner mechanical misalignment. The implementation is based on the algorithm proposed by Feldkamp et al. and is directed at circular scan paths. The algorithm has been developed for the purpose of reconstructing volume data from projections acquired in an experimental x-ray micro-tomography (microCT) scanner. To mathematically model misalignment we use matrix nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Many methods have been proposed for the measurement of the misalignment parameters from the analysis of the acquisition data in cone beam geometry (Beque et al, 2003;Defrise et al, 2008;Noo et al, 2000;von Smekal et al, 2004;Yang et al, 2006). Such parameters can be embedded into the reconstruction process in order to produce misalignment-free reconstructed images (Karolczak et al, 2001).…”
Section: Misalignment Artifactsmentioning
confidence: 99%
“…Many methods have been proposed for the measurement of the misalignment parameters from the analysis of the acquisition data in cone beam geometry (Beque et al, 2003;Defrise et al, 2008;Noo et al, 2000;von Smekal et al, 2004;Yang et al, 2006). Such parameters can be embedded into the reconstruction process in order to produce misalignment-free reconstructed images (Karolczak et al, 2001).…”
Section: Misalignment Artifactsmentioning
confidence: 99%
“…1,7,14 It was reported that 3D images obtained using the cone-beam scanners are inevitably distorted away from the central slice as the single-orbit cone beam geometry does not provide a complete data set. 9,13 These distortions and the associated loss of spatial resolution are particularly evident in samples containing plate-shaped structures, and are minimized by reducing the cone-beam angle. 5,9,13 However, a smaller cone-beam angle has often been found to be associated with lesser number of scanning fields and lower resolution.…”
Section: Introductionmentioning
confidence: 99%
“…9,13 These distortions and the associated loss of spatial resolution are particularly evident in samples containing plate-shaped structures, and are minimized by reducing the cone-beam angle. 5,9,13 However, a smaller cone-beam angle has often been found to be associated with lesser number of scanning fields and lower resolution. This was attributed to the limitation of the distances between the object, X-ray tube, and detectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, application of electrocardiogram-gated 4D-CTA to assess the dynamics of aneurysm wall has shown certain limitations, the most significant of which was various visual artifacts. 3,4 We therefore developed a novel 4-dimensional visualizing technique, dynamic 4D-CTA (DFA), to more accurately evaluate the dynamics of motion in cerebral aneurysms.…”
mentioning
confidence: 99%